How many animal-pollinated angiosperms are nectar-producing? - Ballarin, Caio S. [UNESP]; Fontúrbel, Francisco E.; Rech, André R.; Oliveira, Paulo E.; Goés, Guilherme Alcarás [UNESP]; Polizello, Diego S. [UNESP]; Oliveira, Pablo H. [UNESP]; Hachuy-Filho, Leandro [UNESP]; Amorim, Felipe W. [UNESP] (Wiley, 2024)
The diversity of plant–pollinator interactions is grounded in floral resources, with nectar considered one of the main floral rewards plants produce for pollinators. However, a global evaluation of the number of animal-pollinated nectar-producing angiosperms and their distribution world-wide remains elusive. We compiled a thorough database encompassing 7621 plant species from 322 families to estimate the number and proportion of nectar-producing angiosperms reliant on animal pollination. Through extensive sampling of plant communities, we also explored the interplay between nectar production, floral resource diversity, latitudinal and elevational gradients, contemporary climate, and environmental characteristics. Roughly 223 308 animal-pollinated angiosperms are nectar-producing, accounting for 74.4% of biotic-pollinated species. Global distribution patterns of nectar-producing plants reveal a distinct trend along latitudinal and altitudinal gradients, with increased proportions of plants producing nectar in high latitudes and altitudes. Conversely, tropical communities in warm and moist climates exhibit greater floral resource diversity and a lower proportion of nectar-producing plants. These findings suggest that ecological trends driven by climate have fostered the diversification of floral resources in warmer and less seasonal climates, reducing the proportion of solely nectar-producing plants. Our study provides a baseline for understanding plant–pollinator relationships, plant diversification, and the distribution of plant traits.
Keywords: animal pollination; climate; floral resources; latitudinal gradient; nectar-producing plants; plant diversity; pollinator community; rewards